Technology adoption and farmer efficiency in multiple crops production in eastern Ethiopia: a comparison of parametric and non-parametric distance functions - Alene, Arega D.; Zeller, M. (2005)
(PDF) and data envelopment analysis (DEA) with applications to adopters of improved cereal production technology in eastern Ethiopia. The results from both approaches revealed substantial technical inefficiencies of production among the sample farmers. Technical efficiency estimates obtained from the two approaches are positively and significantly correlated. However, the DEA approach is shown to be very sensitive to outliers as well as to the choice of orientation. The PDF results are relatively more robust. The results from the preferred PDF approach revealed that adopters of improved technology have average technical efficiencies of 79%, implying that they could potentially raise their food crop production by an average 21% through full exploitation of the potentials of improved varieties and mineral fertilizer. The results confirm that food production even under improved technology involves substantial inefficiency. The paper concludes with a discussion of potential underlying factors influencing farmer efficiency under improved technology, such as poor extension, education, credit, and input supply systems.